Electrokinetic remediation of metal-polluted marine sediments: experimental investigation for plant design. (1st November 2015) - Iannelli, R.; Masi, M.; Ceccarini, A.; Ostuni, M.B.; Lageman, R.; Muntoni, A.; Spiga, D.; Polettini, A.; Marini, A.; Pomi, R.
Abstract: This paper presents the results of an extensive set of laboratory experiments performed to design a demonstrative electrokinetic plant for extracting heavy metals from marine sediments dredged from the Livorno marine harbour. The investigated sediments displayed a high salinity, a high acid neutralization capacity, a low electrical resistivity (0.5 Ωm), a high alkalinity (pH ≈ 8) and a large fraction of fine particles. The target metals were Cd, Cr, Cu, Ni, Pb and Zn at relatively weak and inhomogeneous concentrations with high non-mobile fractions. After an accurate characterization, several screening and full electrokinetic tests were performed using cells of two different sizes, several conditioning agents (HNO3, HCl, H2 SO4, citric acid, oxalic acid, ascorbic acid, EDTA), different applied current intensities and durations. The tests highlighted the need for long treatment times in order to obtain a significant pH reduction, with some appreciable metal removal being attained only after several weeks. The best results were obtained with strong acids used as the conditioning agents, with significant specific effects of each acid, including pronounced resistivity increase (from 0.5 up to 10 Ωm) and a high electroosmotic flow (EOF) with H2 SO4, or a reversed EOF (electroendosmosis), and minor resistivity changes with HNO3 . The use of the obtained data to design a demonstrative plant is also presented in the paper, with considerations on operating parameters such as energy and reagent consumption, characteristics of plant components and required safety measures.